TANGGUNG GUGAT KONTRAKTOR ATAS BANGUNAN YANG RUSAK DAN AKIBAT HUKUMNYA DALAM PERJANJIAN PEMBORONGAN PROYEK PEMERINTAH - Roni .A. Barito (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTIONRonny. A. Barito, Fakultashukum, University 17 August 1945, Samarinda Kalimantan East. Account To Sue Contractor Of Damage Building And Its Legal Consequences In Agreement Contract Government Project. [In] guiding by Double Elviyanti [of] Mas, SH, M.Hum and of Dr. H. Abdul Rokhim, SH, M.Hum.Intention of this research [is] accounting to sue contractor to employer To the result of building in work agreement of contruksi otherwise as according to bestekof[is Solving of dispute if there are to [do] not according to result of building of akiba mistake of contractor sub [party/ side].An agreement of contract in fact represent a[n agreement by which contractor side and employer  side is binding itself each other to execute an work at the price of is certain. Solving of dispute to the to do not according to result of building with bestek can be [done/conducted] in so many way of like passing konsoliasi, mediasi, body of arbitrase, deliberation and or through justice